2017
DOI: 10.1016/j.jaci.2016.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Caddis Fly Allergy in a Hydroelectric Plant Worker, a Classic Association

Abstract: RATIONALE: The interaction between chronic inflammation and neural dysfunction points to an involvement linking the nervous and the immune system in the airways. In particular, environmental exposure to nanoparticles has been associated with an enhanced risk of asthma. But the impact of nanoparticles on neurogenic mechanism remains to be determined. The aim of this study was to identify the impact of nanoparticles on neuro inflammation in a mouse model of allergic asthma. METHODS: Using mice sensitized with ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Adult caddisflies are attracted to both UV and visible spectrums (Kimura and Kuranishi 2020). These flies are sucked into and pulverised by the power turbines and dispersed as aeroallergens (Kraut et al 1994;Miedinger et al 2010;McNulty and Divekar 2017). A recent study has reported that professional cleaning workers exhibit airway inflammation and hypersensativity to caddis fly allergens (Lima et al 2017).…”
Section: Caddis Fly (Rhyacophilidae Stephens)mentioning
confidence: 99%
“…Adult caddisflies are attracted to both UV and visible spectrums (Kimura and Kuranishi 2020). These flies are sucked into and pulverised by the power turbines and dispersed as aeroallergens (Kraut et al 1994;Miedinger et al 2010;McNulty and Divekar 2017). A recent study has reported that professional cleaning workers exhibit airway inflammation and hypersensativity to caddis fly allergens (Lima et al 2017).…”
Section: Caddis Fly (Rhyacophilidae Stephens)mentioning
confidence: 99%